Legal Consequences of Excessive Compensation in Hotel Consumer Disputes: Case No. 649/Pdt.G/2023/PN Jkt.Pst - Sheren Christabella; Paulina Shelly Kwu; Velliana Tanaya; Elena Philomena Lee (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The rapid expansion of the hospitality sector has introduced complex legal issues related to hotel liability in maintaining guest safety and comfort. This research examines hotel liability for losses caused by employee negligence and examines the classification and application of material and immaterial damages within Indonesian civil law, with a particular focus on “Decision No. 649/Pdt.G/2023/PN Jkt.Pst.” Using a normative juridical approach with a statutory analysis, this study reviews the Consumer Protection Law (Law No. 8 of 1999) and the Indonesian Civil Code, supported by scholarly literature. The results indicate that negligence committed by hotel employees satisfies the elements of an unlawful act as stipulated in Articles 1365, 1366, and 1367 of the Civil Code, establishing the hotel’s responsibility under both tort and consumer protection frameworks. Nevertheless, the court’s reasoning reveals inconsistencies in categorizing compensation, where certain tangible losses were erroneously treated as intangible damages. Such misclassification risks overlapping claims and excessive restitution, which contradicts the principles of fairness and proportionality. This study contributes by critically evaluating how Indonesian courts distinguish between material and immaterial damages, highlighting the risks of misclassification concerning compensation classification, underscoring the importance of legal certainty, substantive justice, and the preventive as well as educative roles of compensation. The findings are expected to enrich the development of civil law and strengthen consumer protection mechanisms within Indonesia’s hospitality industry.